(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
this article examines comprehensive mechanisms for broadening the tax base and reducing the shadow economy under accounting digitalization through an integrated finance, accounting, and institutional governance perspective. It combines recent international standards discussions, Uzbekistan’s 2021-2025 digitalization trajectory, and analytical mechanisms linking data quality with transparency outcomes. The study argues that digital architecture produces durable anti-shadow effects only when artificial intelligence, professional judgment, and compliance design are aligned within accountable institutions.